Aflatoxin M1 Contamination of Ghanaian Traditional Soft Cottage Cheese (Wagashie) and Health Risks Associated with Its Consumption - Nii Korley Kortei; Theophilus Annan (Journal of Food Quality)
Wagashie is an unripened traditional cheese consumed in West Africa including Ghana. Being a milk product, it is unfortunately susceptible to aflatoxin M1 (AFM1) contamination, which is indeed a grave health challenge globally. This study evaluated AFM1 levels and health risk characterization associated with wagashie (n = 182) sampled from different locations in Ghana. AFM1 was measured with high-performance liquid chromatography with a fluorescence detector (HPLC-FLD). Risk assessments were also conducted using models prescribed by the Joint FAO/WHO Expert Committee on Food Additives (JECFA). Out of the 182 samples analyzed for AFM1, 93/182 (51.1%) tested positive between the range 0.00 ± 0.00–3.60 ± 0.99 µg/kg. Risk assessments of AFM1 using deterministic models produced outcomes that ranged between 0.11 and 3.60 ng/kg bw/day, 0.09–1.54, 0–0.0323 ng aflatoxins/kg bw/day, and 3.5 x 10−3 −0.06 cases/100,000 person/yr for estimated daily intake (EDI), margin of exposure (MOE), average potency, and cancer risks, respectively, for the age categories investigated. It was established that the consumption of wagashie posed adverse health effects on all age categories in the selected regions of the study because all calculated MOE values were less than 100,000. Therefore, contamination of wagashie with AFM1 should be a serious public health concern and as such considered a high precedence for Ghana’s risk management actions.